1989
DOI: 10.1136/bmj.299.6691.85
|View full text |Cite
|
Sign up to set email alerts
|

Mental distress and social conditions and lifestyle in northern Norway.

Abstract: months of follow-up of 187,783 men I. Total mortality. JAMIA 1958;166: 1159-72. 27 Doll R, Peto R. Mortality in relation to smoking: 20 years' observations on male British doctors. BrMedJ 1976;ii:1525-36. 28 Stander R. Influence of treatment of "mild" hypertension on coronary heart disease. Acta Med Scand 1958;701(suppl)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 20 publications
0
10
0
1
Order By: Relevance
“…Although the rationale of abstracting three questions from the General Health Questionnaire could be argued, the decision to do so was based on a report that showed the three included questions to be good predictors of potential depression in the community. 13 The remaining health symptoms were those found to be associated with fibromyalgia in studies undertaken before the initial 1990 survey -for example, those of Campbell et al 14 However, it has been argued that, given the range of personal experiences and characteristics, and the social, economic, and cultural factors that influence pain perception, any study hoping to shed light on the causes or persistence of CWP should investigate all these areas for potential risk factors. 15 16 Subsequent community studies examining predictors of onset and persistence of fibromyalgia have shown the importance of factors such as illness behaviour, and (with more thorough evaluation than was available in this study) psychological distress, somatic symptoms, and fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Although the rationale of abstracting three questions from the General Health Questionnaire could be argued, the decision to do so was based on a report that showed the three included questions to be good predictors of potential depression in the community. 13 The remaining health symptoms were those found to be associated with fibromyalgia in studies undertaken before the initial 1990 survey -for example, those of Campbell et al 14 However, it has been argued that, given the range of personal experiences and characteristics, and the social, economic, and cultural factors that influence pain perception, any study hoping to shed light on the causes or persistence of CWP should investigate all these areas for potential risk factors. 15 16 Subsequent community studies examining predictors of onset and persistence of fibromyalgia have shown the importance of factors such as illness behaviour, and (with more thorough evaluation than was available in this study) psychological distress, somatic symptoms, and fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…We totalled the number of items that seemed to be favourable for mental and physical health of each subject and investigated the relationship with a total of 11 different perceived mental health symptoms. As for lifestyle factors, several studies have reported their influence on mental health by multivariate analyses (Cohen, Schwartz, Bromet, & Parkinson, 1991;Hansen & Jacobsen, 1989). As a comprehensive score of lifestyle, Morimoto et al recommended the Health Practice Index including working hours, and Breslow et al also recommended seven good health habits.…”
Section: Discussionmentioning
confidence: 99%
“…Females rated less type A behavior and hostility than males [51]. Accordingly, in a cross-sectional survey of risk factors for CHD, 13% of men and 17% of women reported having mental distress [52]. There were no distinct differences between the age groups.…”
Section: Resultsmentioning
confidence: 99%
“…There were no distinct differences between the age groups. Single people, separated and divorced people and those who reported that the financial situation of the family during their childhood was difficult reported more mental problems [52]. Furthermore, in an investigation of possible triggers of acute myocardial infarction, the most common triggers were emotional upset (18%) and moderate physical activity (14%) [53].…”
Section: Resultsmentioning
confidence: 99%